(untitled) (Health Renaissance, 2016)
Background: Multicystic nephroma (MCN) is an uncommon but distinctive benign pediatric renal neoplasm but may present clinically at any age. It is scantily reported in the literature. To the best of our knowledge it has not yet been reported from Nepal. It is characterized by a well circumscribed mass with nodular outer surface that contain multiple fluid filled locals. Microscopy show cystically dilated spaces lined by flattened to columnar epithelium and is separated by fibroblastic stroma. A hobnail pattern is common. Case description: Here we report two cases of multicystic nephroma in a span of seven years. The first case is of a one year old female child who was diagnosed of having huge left sided renal mass clinically and the second case is of a 35-year-old male revealing hydatid cyst in USG, CT scan and IVP. Both of them underwent nephrectomy and their microscopic examination revealed typical characteristics of a multicystic nephroma. Conclusion: Since MCN has a benign behaviour it must be differentiated from focal cystic neoplastic lesions, including cystic partially differentiated nephroblastoma (CPDN), which has a low but distinct capability for local recurrence; from Wilm’s tumour with cystic change; and cystic renal cell carcinoma. Health Renaissance 2014;12(3): 227-229